Suberoylanilide Hydroxamic Acid (SAHA) Treatment Reveals Crosstalk Among Proteome, Phosphoproteome, and Acetylome in Nasopharyngeal Carcinoma Cells - Huang, Huichao; Fu, Ying; Duan, Yankun; Zhang, Ye; Lu, Miaolong; Chen, Zhuchu; Li, Maoyu; Chen, Yongheng (Frontiers in Genetics, 2022)
Suberoylanilide hydroxamic acid (SAHA), a famous histone deacetylase (HDAC) inhibitor, has been utilized in clinical treatment for cutaneous T-cell lymphoma. Previously, the mechanisms underlying SAHA anti-tumor activity mainly focused on acetylome. However, the characteristics of SAHA in terms of other protein posttranslational modifications (PTMs) and the crosstalk between various modifications are poorly understood. Our previous work revealed that SAHA had anti-tumor activity in nasopharyngeal carcinoma (NPC) cells as well. Here, we reported the profiles of global proteome, acetylome, and phosphoproteome of 5–8 F cells upon SAHA induction and the crosstalk between these data sets. Overall, we detected and quantified 6,491 proteins, 2,456 phosphorylated proteins, and 228 acetylated proteins in response to SAHA treatment in 5–8 F cells. In addition, we identified 46 proteins exhibiting both acetylation and phosphorylation, such as WSTF and LMNA. With the aid of intensive bioinformatics analyses, multiple cellular processes and signaling pathways involved in tumorigenesis were clustered, including glycolysis, EGFR signaling, and Myc signaling pathways. Taken together, this study highlighted the interconnectivity of acetylation and phosphorylation signaling networks and suggested that SAHA-mediated HDAC inhibition may alter both acetylation and phosphorylation of viral proteins. Subsequently, cellular signaling pathways were reprogrammed and contributed to anti-tumor effects of SAHA in NPC cells.